I'm trying to find the linear fractional transformation that maps points
z1 = -i, z2 = 0, z3 = i onto points w1 = -1, w2 = i, w3 = 1.
I have set it up using the form:
(w-w1)(w2-w3) / (w-w3)(w2-w1) = (z-z1)(z2-z3) / (z-z3)(z2-z1) such that in my example (w+1)(i-1) / (w-1)(i+1) = (z+i)(0-i) / (z-i)(i).
Multiplying the left side by (i-1) / (i -1), I have i[(w+1) / (w-1)] = the right side of the equation above.
Getting rid of the i on the left side, I have (w+1)/(w-1) = i[(z+i)/(z-i)].
I'm stuck at the point where I have: (w+1)(z-i) = (-iz - 1)(w-1). Is this correct, and what do the final steps look like from here?